Surface modification of aluminium alloys by atmospheric pressure plasma treatments for enhancement of their adhesion properties - Mui, T. S M [UNESP]; Silva, L. L G [UNESP]; Prysiazhnyi, V. [UNESP]; Kostov, K. G. [UNESP] (Elsevier, 2017)
This work deals with surface modification of aluminium alloy AA7075 by two types of atmospheric pressure plasma: dielectric barrier discharge (DBD) and atmospheric pressure plasma jet (APPJ) with the purpose to enhance the adhesion of polyurethane coating on the alloy. The surface characterization was performed by using water contact angle, roughness and surface free energy measurements. Quality of the coating was tested according to the adhesion tape test (ASTM D3359) and evaluated by electrochemical techniques. The aluminium alloy showed great improvement of the surface wettability after plasma treatments. While, the adhesion tape test presented excellent results with perfect adhesion, meaning that both plasma treatments were efficient in improving the adhesion of the polyurethane coating to the AA7075. The Fourier Transform Infrared Spectroscopy (FTIR) results demonstrated that the plasma treatment cleaned the Al alloy surface by removing hydrocarbon contaminations. Both polarization curves and Electrochemical Impedance Spectroscopy (EIS) results showed better characteristics of corrosion resistance for polyurethane-coated AA7075 than untreated coated samples.
Keywords: AA7075; Aluminium alloy; APPJ; DBD; Plasma; Surface treatment